Safety and efficacy of everolimus with exemestane vs. Exemestane alone in elderly patients with HER2-negative, hormone receptor-positive breast cancer in BOLERO-2 - Kathleen I. Pritchard (2018)
Background Postmenopausal women with hormone receptor-positive (HR+) breast cancer in whom disease progresses or there is recurrence while taking a nonsteroidal aromatase inhibitor (NSAI) are usually treated with exemestane (EXE), but no single standard of care exists in this setting. The BOLERO-2 trial demonstrated that adding everolimus (EVE) to EXE improved progression-free survival (PFS) while maintaining quality of life when compared with EXE alone. Because many women with HR+advanced breast cancer are elderly, the tolerability profile of EVE plus EXE in this population is of interest. Patients and Methods BOLERO-2, a phase III randomized trial, compared EVE (10 mg/d) and placebo (PBO), both plus EXE (25 mg/d), in 724 postmenopausal women with HR+advanced breast cancer recurring/progressing after treatment with NSAIs. Safety and efficacy data in elderly patients are reported at 18-month median follow-up. Results Baseline disease characteristics and treatment histories among the elderly subsets (≥ 65 years, n = 275; ≥ 70 years, n = 164) were generally comparable with younger patients. The addition of EVE to EXE improved PFS regardless of age (hazard ratio, 0.59 [≥ 65 years] and 0.45 [≥ 70 years]). Adverse events (AEs) of special interest (all grades) that occurred more frequently with EVE than with PBO included stomatitis, infections, rash, pneumonitis, and hyperglycemia. Elderly EVE-treated patients had similar incidences of these AEs as did younger patients but had more on-treatment deaths. Conclusion Adding EVE to EXE offers substantially improved PFS over EXE and was generally well tolerated in elderly patients with HR+advanced breast cancer. Careful monitoring and appropriate dose reductions or interruptions for AE management are recommended during treatment with EVE in this patient population. © 2013 Elsevier Inc. All rights reserved.